Changes in symptoms, sleep, oxidative stress, and inflammatory markers among community-dwelling stroke survivors after a tai chi exercise intervention. (29th July 2021) - Taylor-Piliae, R; Morrison, H; Hsu, C-H; Grandner, M
Abstract: Funding Acknowledgements: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Laurence B. Emmons Research Award Background: Depression is prevalent among one-third to two-thirds of stroke survivors. Despite the availability of pharmacotherapies and/or psychotherapies, depression persists, even 5-10 years post-stroke, reflecting limited treatment responses and/or adherence to this conventional care. Mind-body interventions are commonly used among adults to ameliorate depressive symptoms, thus we investigated the feasibility of Tai Chi, alongside conventional care, to manage post-stroke depression. Purpose: Describe changes in symptoms of depression, anxiety and stress, sleep, oxidative stress, and inflammatory markers post-intervention among community-dwelling stroke survivors with depressive symptoms. Methods: In this feasibility study, a single-group pre-post intervention design was used. Due to COVID-19, participants attended a 1-hour Tai Chi exercise class three times per week for 8 weeks, instead of the planned 12-weeks. Symptoms of depression, anxiety and stress were assessed using standardized questionnaires (Center for Epidemiological Studies Depression scale, CESD; Generalized Anxiety Disorder Assessment; Perceived Stress Scale), objective sleep was assessed via a research-grade triaxial accelerometer (ActiGraph GT9X), and blood samples were taken to assess oxidative stress (plasma superoxide dismutase, SOD)  and inflammatory markers (serum tumor necrosis factor-alpha, interleukin-6, interleukin-10). Pre-post intervention changes were assessed using paired t-tests. Results: Community-dwelling stroke survivors (N = 11) on average 69.7 ± 9.3 years old, mainly retired (73%, n = 8), married men (55%, n = 6) with >13 years education (91%, n = 10), reporting depression symptoms (CESD = 17.3 ± 11.4) and 55% taking anti-depressant medications, enrolled. The majority of participants reported having an ischemic stroke (82%, n = 9) with hemiparesis (55%, n = 6), but were able to walk 15 feet without assistance (91%, n = 10). After the Tai Chi intervention, we observed significant reductions in symptoms of depression (-5.3 ± 5.9, p = 0.01), anxiety (-2.2 ± 2.4, p = 0.01) and stress (-4.6 ± 4.8, p = 0.01); along with better sleep efficiency (+1.8 ± 1.8, p = 0.01), less wakefulness after sleep onset (-9.3 ± 11.6, p = 0.04), and less time awake (-9.3 ± 11.6, p = 0.04). In addition, there was a 36% decrease in SOD activity (p = 0.02) indicative of a decreased oxidative environment post-intervention; though no significant changes in any of the inflammatory markers were found (all p-values >0.05). Conclusion: Symptoms of depression, anxiety and stress were observed in these community-dwelling stroke survivors along with sub-optimal sleep. Among community-dwelling stroke survivors, Tai Chi exercise is a feasible intervention that can be used alongside conventional care to manage post-stroke depression and may also aid in reducing symptoms of anxiety and stress, and improve sleep.  Further research is needed with rigorous study designs and larger samples, before widespread recommendations can be made.